The leader who had no title : a modern fable on real success in business and in life - Sharma, Robin S. (Robin Shilp), 1964- (New York : Free Press, 2010)
Told in first-person story form, this fable follows a man named Blake through the four lessons he learns to become a great leader and a great person.
Includes bibliographical references.
Keywords: Leadership